PERBANDINGAN METODE MANUFAKTUR PROPELLER CLARK Y: 3D PRINTING DAN SILICONE MOLDING - Ikbal Rizki Putra; Ll. Aghyl Anugerah Mahesa; Sehono; Gaguk Marausna; Gilang Argya Dyaksa; Fajar Yulianto Prabowo; Brian Teo Putra (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
Currently, the aviation industry is experiencing rapid growth, not only in manned aircraft but also in the development of Unmanned Aerial Vehicles (UAVs). One of the crucial components in UAVs is the propeller. Common manufacturing methods for propellers include forming, hand lay-up, and vacuum bagging. Alternative methods with promising potential include silicone molding and three-dimensional (3D) printing. This study aims to determine the most suitable manufacturing method for producing a propeller with a Clark Y airfoil type. The research was conducted using simulation, geometric analysis, and visual analysis. The silicone molding method can serve as an alternative to injection molding, as the dimensional difference between the CAD design and the final product is relatively minor, with the maximum shrinkage recorded at -8.77%. Meanwhile, the 3D printing method is more appropriate when the airfoil thickness is greater.